Neurocardiogenic (Vasovagal) Syncope - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
A retrospective analysis of 54 consecutive patients with recurrent syncope, examined with or without tilt table testing, is reported from the Children's Heart Center, Egleston Children's Hospital, Emory University, Atlanta, GA.